Vision based control of multi-robot system - Oh, Matthew Han Xiong (2014)
In recent years, technology has evolved so rapidly that systems are becoming more and more complex. In particular, in the field of control robotics, a single control robot may no longer be able to fulfil the requirements of a complex task. This led to increase development in the area of formation control of network multi-robot system.This project presents different formation controllers for a multi-robot system. In order to test out different formation controllers, a testbed was designed. Mobile robots with in-build communications capabilities were also used for this purpose. To allow scalability for the system, communication limitations in large network multi-robots system were addressed. The result is a distributed formation controller.The distributed formation controller is actually a superset of all other controllers. It consists of an estimator which construct the desired reference for each robot based on information exchange by neighbouring robots. It also consists of a region based control for trajectory tracking which includes relative velocity estimation.However, one major downside of the testbed includes undesirable computation speed of the microcontroller. In order to overcome this issue, actual computations are emulated in the central processing system before transferring to the mobile robots.To employ a more effective system, it is recommended to use holonomic drive for more effective steering and communication platform that allows inter-communication between robots.In conclusion, for future development of large scaled multi-robot control, mobile vision-based multi-robot system can be incorporated for effective positioning. It is also strongly recommended to have a robust system with small number of robots before proceeding in scaling up.